Walnut polyphenol extracts inhibit Helicobacter pylori-induced STAT3(Tyr705) phosphorylation through activation of PPAR-γ and SOCS1 induction - Park, Jong Min (J Clin Biochem Nutr, 2020)
The health beneficial effects of walnut plentiful of n-3 polyunsaturated fatty acid had been attributed to its anti-inflammatory and anti-oxidative properties against various clinical diseases. Since we have published Fat-1 transgenic mice overexpressing 3-desaturase significantly mitigated Helicobacter pylori (H. pylori)-associated gastric pathologies including rejuvenation of chronic atrophic gastritis and prevention of gastric cancer, in this study, we have explored the underlying molecular mechanisms of walnut against H. pylori infection. Fresh walnut polyphenol extracts (WPE) were found to suppress the phosphorylation and nuclear translocation of signal transducer and activator of transcription 3 (STAT3) induced by H. pylori infection in RGM-1 gastric mucosal cells. Notably, H. pylori infection significantly decreased suppressor of cytokine signaling 1 (SOCS1), but WPE induced expression of SOCS1, by which the suppressive effect of walnut extracts on STAT3(Tyr705) phosphorylation was not seen in SOCS1 KO cells. WPE induced significantly increased nuclear translocation nuclear translocation of PPAR-γ in RGM1 cells, by which PPAR-γ KO inhibited transcription of SOCS1 and suppressive effect of WPE on p-STAT3(Tyr705) was not seen. WPE inhibited the expression of c-Myc and IL-6/IL-6R signaling, which was attenuated in the RGM1 cells harboring SOCS1 specific siRNA. Conclusively, WPE inhibits H. pylori-induced STAT3 phosphorylation in a PPAR-γ and SOCS1-dependent manner.